Qualification of conductive adhesives for photovoltaic application - accelerated ageing tests. (September 2017) - Bauermann, Luciana Pitta; Fokuhl, Esther; Stecklum, Sandor; Philipp, Daniel; Geipel, Torsten; Kraft, Achim; Eitner, Ulrich; Fischer, Thomas; Breitenbücher, Dieter
Abstract: In order to achieve a fast and reliable qualification of promising conductive adhesives for solar cells, different accelerated ageing test sequences, accompanied with analyses on material level are conducted. Damp-heat followed by damp heat at a current range of 8 A; humidity freeze and thermal cycling. The testing procedure in the herein presented work is adapted to identify advantages and also weaknesses of the materials in combination with the entire design. The conductive adhesives replace the lead-based soldering thereby allowing a lower processing temperature. Another potential reduction of material costs is the use of double redundant fingers instead of busbars. In this way, a considerably smaller amount of silver is needed. The interconnectors are glued between theses double redundant fingers with the conductive adhesive. Another advantage of the gluing is the possibility of using groove structured interconnectors that allow an increase in power of the solar module by reflecting light back to the solar cell. As major degradation indicator the performance of the modules containing conductive adhesives, redundant fingers and groove structured interconnectors is measured before and after the exposition of the solar module to different accelerated ageing tests and compared to the reference solar module with flat interconnectors soldered on busbars. After the accelerating ageing test damp heat (DH), there was already a clear difference in viability of the conductive adhesives. For two conductive adhesives, module power losses were comparable to the reference, for a third one power losses amounted to 14 %. The loss in power is caused by an increase in serial resistance. Analyses of the adhesives indicate a relation between the degradation in damp-heat and the adsorption of humidity of the material. Different subsequent aging tests (after DH) showed the feasibility of this innovative technology, but also unveiled weaknesses compared to a traditional soldered busbar technology. Two of the three conductive adhesives have fulfilled the IEC 61215 criteria in terms of power loss after damp heat, humidity freeze and thermal cycling.